2019
DOI: 10.1039/c9na00395a
|View full text |Cite
|
Sign up to set email alerts
|

Surface group-modified MXene nano-flake doping of monolayer tungsten disulfides

Abstract: A new chemical (MXene) doping strategy to modulate the exciton and trion for achieving high photoluminescence (PL) efficiency of WS2 is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Previously, Tao et al demonstrated that the charge transfer ability of Ti 3 C 2 T x can be controlled by introducing different types of surface functional groups. 67 They constructed WS 2 /Ti 3 C 2 T x heterostructure and showed that F-MXene has more efficient charge transfer than N-MXene. Thus, our findings demonstrate the potential of F-MXene to tune the electronic structure of perovskite-based optoelectronic devices effectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Tao et al demonstrated that the charge transfer ability of Ti 3 C 2 T x can be controlled by introducing different types of surface functional groups. 67 They constructed WS 2 /Ti 3 C 2 T x heterostructure and showed that F-MXene has more efficient charge transfer than N-MXene. Thus, our findings demonstrate the potential of F-MXene to tune the electronic structure of perovskite-based optoelectronic devices effectively.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Tao et al revealed the MXenes' ability to regulate the trion-to-exciton transition of WS 2 via a charge transfer mechanism, resulting in a fivefold enhancement in photoluminescence efficiency. [256] They showed that upon drop-casting Fterminated Ti 3 C 2 T x on WS 2 , the neutral exciton peak becomes dominant compared to the negative trion peak, owing to the electron transfer from WS 2 to Ti 3 C 2 T x . Furthermore, by reducing the F-terminations on Ti 3 C 2 T x MXene via thermal annealing, the electron-withdrawing ability of Ti 3 C 2 T x was weakened, resulting in lower photoluminescence enhancement compared to F-terminated Ti 3 C 2 T x .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Constructing multifunctional hybrid heterostructures with a different and fruitful band alignment will undoubtedly break the limitation and expands the range of the spectral response beyond the bandgap of individual materials. [ 237 ] In particular, type‐II band alignment between 2D semiconductors can facilitate the interlayer excitation and transition of sub‐bandgap photons at the telecommunication wavelength. A novel vdW TMD‐based photodiode composed of (n‐BP/p‐PdSe 2 ) exhibits a gate tunable and very high photoresponsivity of 4.53 × 10 5 and 1.63 × 10 5 A W −1 under a NIR wavelength of 1064 and 1310 nm, respectively, together with high detectivity and EQE.…”
Section: D Heterostructures For Ir Detectionmentioning
confidence: 99%